A preliminary study on the post-secondary school students’ language learning strategies / Surina Nayan and Hariharan N. Krishnasamy - Nayan, Surina; N. Krishnasamy, Hariharan (2018)
One of the factors that determines students’ success in learning a language, is through their correct choices of strategy used. The study aims at identifying the students’ language learning strategies. The respondents were 48 diploma students from two different diploma programmes which are Diploma in Polymer Science and Diploma in Sports Recreation. The researcher adapts Edvardsdóttir’s (2010) questionnaire in acquiring the information needed for the study. The findings reveal that students from both programmes preferred guessing from context, asking their classmates, using google and using an on-line dictionary. On the other hand, they rarely seek their lecturer’s help in finding the meanings of words and they would rather seek others help. Future research should consider the use of a semi-structured interview with the respondents as to find the reasons why they preferred some strategies as compared to the others.